Optineurin and amyotrophic lateral sclerosis. Issue 3 (26th December 2012) - Maruyama, Hirofumi; Kawakami, Hideshi
<x xml:space="preserve">Abstract</x> Amyotrophic lateral sclerosis is a devastating disease, and thus it is important to identify the causative gene and resolve the mechanism of the disease. We identified optineurin as a causative gene for amyotrophic lateral sclerosis. We found three types of mutations: a homozygous deletion of exon 5, a homozygous Q398X nonsense mutation and a heterozygous E478G missense mutation within its ubiquitin‐binding domain. Optineurin negatively regulates the tumor necrosis factor‐α‐induced activation of nuclear factor kappa B. Nonsense and missense mutations abolished this function. Mutations related to amyotrophic lateral sclerosis also negated the inhibition of interferon regulatory factor‐3. The missense mutation showed a cyotoplasmic distribution different from that of the wild type. There are no specific clinical symptoms related to optineurin. However, severe brain atrophy was detected in patients with homozygous deletion. Neuropathologically, an E478G patient showed transactive response DNA‐binding protein of 43 kDa‐positive neuronal intracytoplasmic inclusions in the spinal and medullary motor neurons. Furthermore, Golgi fragmentation was identified in 73% of this patient's anterior horn cells. In addition, optineurin is colocalized with fused in sarcoma in the basophilic inclusions of amyotrophic lateral sclerosis with fused in sarcoma mutations, and in basophilic inclusion body disease. These findings strongly suggest that optineurin is involved in the pathogenesis of amyotrophic lateral sclerosis. Geriatr Gerontol Int 2013; 13: 528–532.